Study on Vibration Characteristic of Trilobe Raceway Cylindrical Roller Bearing with Elastic Support - Sun Xue; Deng Sier; Zhang Yuanjun; Chen Guoding (Jixie chuandong)
Based on dynamics analysis of rolling bearing,the dynamics differential equations for cylindrical roller bearing with trilobe raceway and elastic support are established. By using the predict-correct integer algorithm with variable step,the dynamics equation is solved,and the influence of structural parameters of elastic support and working conditions on the vibration characteristics of the bearing is investigated. The results show,that the inter-groove number,thickness circular beam and transition angle of elastic support have significantly effect on the vibration of bearings,but gap of groove has little effect on it. In a certain range of load and rotation speed,elastic ring can effectively decrease the vibration of bearing,elastic support with lesser inter-grooves can enlarge its impact-absorb range of load and speed,the elastic support also can reduce the bearing vibration caused by the impact load.